The promiscuous development of an unconventional Qa1b-restricted T cell population - Michael Manoharan Valerio; Kathya Arana; Jian Guan; Shiao Wei Chan; Xiaokun Yang; Nadia Kurd; Angus Lee; Nilabh Shastri; Laurent Coscoy; Ellen A. Robey (Frontiers in Immunology, 2023)
MHC-E restricted CD8 T cells show promise in vaccine settings, but their development and specificity remain poorly understood. Here we focus on a CD8 T cell population reactive to a self-peptide (FL9) bound to mouse MHC-E (Qa-1b) that is presented in response to loss of the MHC I processing enzyme ERAAP, termed QFL T cells. We find that mature QFL thymocytes are predominantly CD8αβ+CD4-, show signs of agonist selection, and give rise to both CD8αα and CD8αβ intraepithelial lymphocytes (IEL), as well as memory phenotype CD8αβ T cells. QFL T cells require the MHC I subunit β-2 microglobulin (β2m), but do not require Qa1b or classical MHC I for positive selection. However, QFL thymocytes do require Qa1b for agonist selection and full functionality. Our data highlight the relaxed requirements for positive selection of an MHC-E restricted T cell population and suggest a CD8αβ+CD4- pathway for development of CD8αα IELs.